Genome-Wide Identification of the AP2/ERF Gene Family and Functional Analysis of GmAP2/ERF144 for Drought Tolerance in Soybean - Wang, Haitang; Ni, Danqing; Shen, Jiacheng; Deng, Sushuang; Xuan, Huidong; Wang, Congcong; Xu, Jianyu; Zhou, Li; Guo, Na; Zhao, Jinming; Xing, Han (Frontiers in Plant Science, 2022)
Drought is a major environmental constraint that causes substantial reductions in plant growth and yield. Expression of stress-related genes is largely regulated by transcription factors (TFs), including in soybean (Glycine max (L.) Merr.). In this study, 301 GmAP2/ERF genes that encode TFs were identified in the soybean genome. The TFs were divided into five categories according to their homology. Results of previous studies were then used to select the target gene GmAP2/ERF144 from among those up-regulated by drought and salt stress in the transcriptome. According to respective tissue expression analysis and subcellular determination, the gene was highly expressed in leaves and encoded a nuclear-localized protein. To validate the function of GmAP2/ERF144, the gene was overexpressed in soybean using Agrobacterium-mediated transformation. Compared with wild-type soybean, drought resistance of overexpression lines increased significantly. Under drought treatment, leaf relative water content was significantly higher in overexpressed lines than in the wild-type genotype, whereas malondialdehyde content and electrical conductivity were significantly lower than those in the wild type. Thus, drought resistance of transgenic soybean increased with overexpression of GmAP2/ERF144. To understand overall function of the gene, network analysis was used to predict the genes that interacted with GmAP2/ERF144. Reverse-transcription quantitative PCR showed that expression of those interacting genes in two transgenic lines was 3 to 30 times higher than that in the wild type. Therefore, GmAP2/ERF144 likely interacted with those genes; however, that conclusion needs to be verified in further specific experiments.